The role of the media in spreading digital awareness among members of society in the Kingdom of Saudi Arabia - Batawi, Faris Omar; Toweirqie, Doaa Hassan (Arab Journal for Sciences and Research Publishing, 2025)
This research aimed to identify the role of Saudi media in spreading digital awareness in Saudi society from the point of view of users of social media and platforms, and to determine the level of digital awareness among users of various social media in the Makkah region from the point of view of individuals in a random sample of society. To achieve these goals, the researchers used the descriptive analytical approach and the questionnaire tool. The sample consisted of (184) individuals, males and females, in the Makkah region, with different levels of educational level, and different age groups from the age of 18 years. The results of the study reached the community's satisfaction (to some extent) with the performance of the media in spreading national awareness among members of society from the point of view of the sample individuals, as their response to the role of the media was promising, and the degree of digital awareness among many members of society increased with the security and culture of digital information. The study recommended the necessity of all state institutions joining forces to participate effectively in order to eliminate the corrupt media directed against Islam and Islamic countries by striking our young men and women in their values and customs.
Keywords: Media; digital awareness; content; community interaction; individuals in Saudi society